Cost Comparison of a Building Project by Manual and BIM - Haider, Usman; Khan, Usama; Nazir, Asif; Humayon, Muhammad (Salehan Institute of Higher Education, 2020)
This article focuses on comparison between Manual/Traditional and Building Information Modelling (BIM) software based approaches for cost comparison. Centre line method for manual and Revit software for BIM based approaches are used in this research. The principal objectives of this research are to calculate quantities by Manual Centre line method, then to make the cost estimation fast, accurate, efficient, and errorless by using BIM software Rivet, and finally the comparison study of manual based and BIM / Software based estimation. For manual approach, quantities are calculated by multiplying the measurements of length, breadth, and height. Then to get the total quantities the deduction is subtracted from the quantities and final BOQ is prepared for which estimated cost of building is calculated. For BIM based approach, 3D model from 2D floor plan of building is prepared in Revit software, then to estimate the cost of building structure elements, sheets of quantities are generated in the schedule option of the view tab in the software. The Percentage difference between Manual and BIM / Revit Software estimation in brick work, RCC Slab, Plaster Work, PCC for Flooring, Floor Tile Work, Skirting, Paint Work, False Ceiling, Doors and Aluminum Work is 4.57, 2.61, 7.58, 3.27, 1.87, 6.73, 8.03, 1.87, and 0.00% respectively. The total cost difference between manual and BIM based estimation approach comes out to be 4.8%. It is thus concluded that the BIM-assisted estimates have better performance over traditional/manual estimating methods.